HUBUNGAN PEMBERIAN REINFORCEMENT DENGAN MOTIVASI BELAJAR SISWA DI SD NEGERI 106158 PEMATANG JOHAR - Surya Andriani; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2020)
The problems in this study are the low motivation of students to learn, the low ability of teachers to create active learning conditions, the lack of positive reinforcement, and the teacher tends to repeat reinforcement on student mistakes. The purpose of this study was to determine the relationship between reinforcement and student motivation at SD Negeri 106158 Pematang Johar. This research is a correlational study, conducted at SD 106158 Pematang Johar in the 2020/2021 academic year with a population of 98 people and a sample of 98 people (= 0.05). The instrument used to obtain research data is a questionnaire of each variable with a Likert Scale. The data analysis technique used in this research is to use the product moment correlation coefficient test, by first testing the requirements such as normality, homogeneity, and linearity tests. Based on the results of the data analysis, it was found that reinforcement was on the moderate criteria (mean = 26.1) and learning motivation was also on the moderate criteria (mean = 42.47). The results of the correlation analysis show rxy = 0.221 while rtable = 0.05 (0.1986) thus it can be said that there is a positive relationship between reinforcement and learning motivation. Furthermore, the results of the t-test obtained 2.22 while the t-table with = 0.05 obtained the value of t-table = 1.98447. Thus, it can be concluded that the higher the reinforcement, the higher the student's learning motivation.